(NsOPOSTAWITELXNYJ SINTAKSIS RUSSKOGO I TATARSKOGO QZYKOW (B/s - (NbAJRAMOWA(B, (NlUIZA kARIMOWNAs; (NsAFIULLINA(B, (NfLERA sADRIEWNAs ((NkAZANX (B:s (NiZD(B-(NWO kAZAN(B. (NUN(B-(NTA(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 191-195s
Keywords: (NrUSSKIJ QZYKs -- (NsINTAKSIS SOPOSTAWITELXNYJs; (NtATARSKIJ QZYKs -- (NsINTAKSIS SOPOSTAWITELXNYJs